سید محمد امین علی شاہ نقوی کے شعری کلام میں اخلاق ِرسولﷺکااختصاصی مطالعہ: A special study of the Morals of the Prophet (PBUH) in the poetry of Syed Muhammad Amin Ali Shah Naqvi - Shama Naz (Al Manhal Research Journal, 2024)
The Holy Prophet's (peace be upon him) life has been described as a practical example of the practical interpretation of the Holy Qur'an and the command of Allah Almighty. With the passage of time, various books of the Holy Prophet's life kept increasing. Many poets have been written on the Holy prophet Muhammad different aspects of his life. Syed Amin Ali Shah is also one such poet to whom due to his work, not only the present era but also the coming era cannot remain without paying tribute. He was not only a master of his words but also a practicing poet. He had mastered not only Urdu but also Arabic, Persian and Punjabi languages ​​and he is seen writing poetry in these natural languages. In Urdu literature, you have the pride of being an oratorical poet.in this article; a special study will be done on the morals of the Prophet (peace be upon him) in the poetry of Syed Muhammad Amin Ali Shah Naqvi.